High-purity 3D nano-objects grown by focused-electron-beam induced deposition. (25th July 2016) - Córdoba, Rosa; Sharma, Nidhi; Kölling, Sebastian; Koenraad, Paul M; Koopmans, Bert
Abstract: To increase the efficiency of current electronics, a specific challenge for the next generation of memory, sensing and logic devices is to find suitable strategies to move from two- to three-dimensional (3D) architectures. However, the creation of real 3D nano-objects is not trivial. Emerging non-conventional nanofabrication tools are required for this purpose. One attractive method is focused-electron-beam induced deposition (FEBID), a direct-write process of 3D nano-objects. Here, we grow 3D iron and cobalt nanopillars by FEBID using diiron nonacarbonyl Fe2 (CO)9, and dicobalt octacarbonyl Co2 (CO)8, respectively, as starting materials. In addition, we systematically study the composition of these nanopillars at the sub-nanometer scale by atom probe tomography, explicitly mapping the homogeneity of the radial and longitudinal composition distributions. We show a way of fabricating high-purity 3D vertical nanostructures of ∼50 nm in diameter and a few micrometers in length. Our results suggest that the purity of such 3D nanoelements (above 90 at% Fe and above 95 at% Co) is directly linked to their growth regime, in which the selected deposition conditions are crucial for the final quality of the nanostructure. Moreover, we demonstrate that FEBID and the proposed characterization technique not only allow for growth and chemical analysis of single-element structures, but also offers a new way to directly study 3D core–shell architectures. This straightforward concept could establish a promising route to the design of 3D elements for future nano-electronic devices.